RELATIONSHIP BETWEEN PARITY AND LABOR WITH BABY BLUES EVENTS IN CLINIC YOSTAVAN MEDIKA SIDOARJO - Anastasia R Ardianis; Maria E Djaputra; Venny Tandyono (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: Parity is the number of children born to the mother and able to live outside the womb. Labor is the birth of the fetus and placenta in sufficient number of month. Maternity blues or post partum blues or baby blues is a depressive syndrome that occurs whitin 14 days which is not too long and will disappear over time whitout treatment.Risk factors in the form of labor due to physical exhaustion during the labor process, and bleeding that can affect the activity of the mother after childbirth. The risk factor is parity due to their lack of experience as primiparous mothers and their inability to properly care for their babies, primiparous mother are more likely to experience the baby blues than multiparous mother. Researchers are interested in conducting research on “The Relationship between Parity and Labor with the Incidence of baby blues at the Clinic Yostavan Medika Prambon, Sidoarjo”.Purpose: Knowing the relationship between parity and labor with the incidence of baby blues in Clinic Yostavan Medika sidoarjoMethod: Cross sectional is used in this research and the sampling method was purposive sampling. This study used the EPDS questionnairewith logistic regression analysis techniques.Result: In the univariate analysis using the bivariate logistic regression test, significant results were obtained with a value of 0,011 which means that parity and delivery are related to the incidence of baby blues. Respondents who experienced the baby blues with primipara parity were as many as 57,6%. Respondents with a normal delivery process who experienced the baby blues 56,7%. Based on the multivariate logistic regression analysis test, the results showed no significant p value = 0.460 which means that parity and delivery have no effect on baby blues.Conclusion: There is not relationship between parity and labor with the incidence of baby blues at Clinic Yostavan Medika, Sidoarjo